Evaluasi Program Penerapan Bimbingan Karir di SMK Negeri 5 Kota Padang - Ferdiansyah; Nizwardi Jalinus; Ambiyar; M. Giatman; Fahmi Rizal (Cakrawala: Jurnal Pendidikan, 2020)
Goals of this study are to describe the context, input, process and product components in guidance career program at SMK Negeri 5 Padang. The study is performing by distributing questionares to the student and interview to the guidance tutor. The type of this research is evaluative research using descriptive qualitative research methods. Based on this study, we can find that the context component has been well programmed as what the student describes 84,01%. Input component has not support the implementation scheduled program which shows by student 68,61%. At process component , as student statement 65,64% shows that process component has not been effective. Product component has not been optimum shows by student statement 69,30%. Generally we can have a conclucion that the implementation career guidance program at SMK Negeri 5 Padang has not been consistent with input and process component to achieve optimum result.